Didactics of volleyball into the educate program for coaches/trainers/technicians of Italian Federation of Volleyball (FIPAV) - Raiola, G. (Journal of Physical Education and Sport, 2012)
This study aims to determine whether the new acquisitions in the field of research on movement and the consequent impact on the paradigms of learning and teaching method have been considered in the education about sport activity. Actually, there is not a deep theoretical and argumentative study on the question of didactics approach to teach, so this study focuses on the new scientific evidences to verify if they are applied on team sport and, first of all, of volleyball. It uses an integrated method that joins theoretical approach on scientific paradigms on motor control and learning and deductive-argumentative approach on the specific didactics. Results do not carry out any particular aspects connected neither to the new neurological theories applied motor control and learning and related didactics. All documents of educate program for coaches, technicians and trainers does not provide any reference of open loop, closed loop and generalized program and its affect on the learning by cognitive approach. In the same way, they does not provide any reference on mirror neurons system, motor imagery and freedom degrees by ecological and dynamic approach. In conclusion this study takes in evidence no update according to new paradigm on theory on motor control and relating methodology to conduct on consequent didactics. It may be useful to deepen further the study by the scientists and experts for the necessary updates to fill up the vacuum.